2017
DOI: 10.18632/oncotarget.16875
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-ketoglutarate suppresses the NF-κB-mediated inflammatory pathway and enhances the PXR-regulated detoxification pathway

Abstract: Alpha-ketoglutarate (AKG) is a critical nutritional factor in the maintenance of intestinal homeostasis. However, the relative mechanism of AKG has not been well understood. It was recently shown that the interaction between nuclear factor kappa B (NF-κB)-mediated inflammatory pathway and pregnane X receptor (PXR)-regulated detoxification pathway is a check and balance mechanism for keeping the homeostatic state of the intestine, preventing the onset of intestinal inflammation which may lead to cancer. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Lactate accumulation in the microenvironment has been shown to suppress cytokine production and migration of human cytotoxic T cells [ 60 , 61 ]. Similarly, α -ketoglutarate has been shown to quell inflammatory processes by suppressing NF- κ B-mediated inflammatory pathways [ 62 ]. Succinate can also modulate inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate accumulation in the microenvironment has been shown to suppress cytokine production and migration of human cytotoxic T cells [ 60 , 61 ]. Similarly, α -ketoglutarate has been shown to quell inflammatory processes by suppressing NF- κ B-mediated inflammatory pathways [ 62 ]. Succinate can also modulate inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…One of our recent studies demonstrates that AKG exert beneficial effects on the modulation of inflammatory cytokines such as IL-2 IL-8, IL-10, TGF-β, TNF-α and IL-17 [ 24 ], which have a negative influence on gut integrity and epithelial restitution when excessively secreted [ 6 ]. This is consistent with our findings that the addition of AKG inhibited the secretion and mRNA expression of IL-1β, IL-6, and IL-12 in the small intestine of LPS-induced piglets, indicating the possible anti-inflammatory effect of enteral supply of AKG during stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al (2015) reported that AKG lowered body weight and affected intestinal innate immunity through influencing intestinal microbiota in mice [ 27 ]. Of note, our group also found that AKG could suppress NF-κB-mediated inflammatory pathway and enhance the PXR-regulated detoxification pathway to improve intestinal immune and self-detoxification system [ 24 , 28 ]. It is further confirmed by our study that AKG as a precursor for the biosynthesis of glutamate and glutamine, inproved the secretion and expression of inflammatory cytokines in response to LPS stimulation, thereby increasing intestinal immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations